Legal Protection for People with Soul Disorders (ODGJ) (Reflection on Handling ODGJ in Ternate City) - Darwis Haris (LEMBAGA PENELITIAN PUBLIKASI DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2023)
Abstrac As part of the citizenry, people with mental disorders (ODGJ) often have their rights neglected. This phenomenon of negligence can be found in almost all urban areas in Indonesia. On the other hand, even though they have limitations in various aspects, their presence in public spaces is not the will of them or their families. The fate they suffer makes their living space socially discriminated against. The city of Ternate is one of the cities in Indonesia that has quite a high incidence of ODGJ, but at the same time the infrastructure and government policies are not yet in favor of protecting them. This condition then causes a number of problems that often arise, such as ODGJ threatening residents due to negligence in monitoring cars, or ODGJ experiencing violence by residents due to the behavior of ODGJ which tends to be disturbing. The limited infrastructure needed to protect people with ODGJ is currently very important to ensure their rights as citizens are fulfilled.